Validation of tuberculosis notification in RSA : an epidemiological analysis of the reported tuberculosis cases and deaths in the period 1993 to 2003 - Matjila, Maila J. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2009.